The Relationship Between Mother’s Occupation And The Health Level of School Supplies for Children Aged 5-7 Years at ABA 33 Karangploso Kindergarten - Putri, Safira Ramadhanti Kurnia; Pramono, Pramono; Manningtyas, Rosyi Damayani Twinsari (Universitas Negeri Malang, 2024)
Abstract This study aims to describe whether the relationship between maternal employment and the level of health of school supplies for children aged 5-7 years at TK ABA 33 Karangploso has a significant relationship or not. This type of research is correlation research with the Eta correlation research type. The location of this research is TK ABA 33 Karangploso with the number of research objects being 36 mothers of students at TK ABA 33 Karangploso. The research was carried out from 17 to 21 June 2024. The data collection technique used a checklist observation sheet. Data analysis techniques using quantitative analysis techniques. The results obtained from this research show that the highest percentage of mothers' work is working as a housewife. The health level of children's school supplies at Kindergarten ABA 33 Karangploso is classified as healthy. And the relationship between mother's employment and the health level of children's school supplies is not related or correlated significantly. Keywords: mother occupation; school supplies; early childhood